Increased monohexosylceramide levels in the serum of established rheumatoid arthritis patients. (6th December 2019) - Miltenberger-Miltenyi, Gabriel; Cruz-Machado, Ana Rita; Saville, Jennifer; Conceição, Vasco A; Calado, Ângelo; Lopes, Inês; Fuller, Maria; Fonseca, João Eurico
Abstract: Objectives: To identify serum sphingolipids that could act as candidate biomarkers in RA. Methods: We performed lipidomic analyses in the serum of 82 participants: 19 established RA patients, 18 untreated early RA patients, 13 untreated early arthritis patients not fulfilling the classification criteria for RA, 12 established SpA patients and 20 controls. We compared the lipid levels from the different patient groups with the control group through multiple-regression analyses controlling for age at diagnosis, gender and medication (cDMARDs and corticoids). Results: Established RA patients had significantly increased levels of sphingosine, monohexosylceramide and ceramide compared with controls, when controlling for age and gender. Monohexosylceramide levels remained significantly increased when additionally controlling for medication. On the contrary, SpA patients had significantly decreased levels of ceramide, in both analyses. Conclusion: We observed a detectable increase in the levels of certain sphingolipids in the serum of established RA patients when compared with controls, in line with previous observations in the synovial fluid. Such findings provide further evidence that sphingolipids may play a key role in the pathophysiology of RA.